Phylogeny and Evolution of African Shrews (Mammalia: Soricidae) Inferred from 16s rRNA Sequences - (:unkn) unknown (My University, 2001)
Current phylogenetic hypotheses on the African Crocidurinae (Soricidae) are based upon morpho-anatomical, karyological, and allozyme studies. The present study attempts to resolve the interrelationships among African Crocidurinae and their relationships to Eurasian Crocidurinae and to the subfamily Soricinae, on the basis of partial mitochondrial 16s rRNA sequences (549 bp). This is the first molecular study to include all but one of the nine currently recognized African shrew genera. In agreement with current views, two major lineages emerge. The first lineage includes Myosorex and Congosorex and supports the existence of a myosoricine taxon. The second lineage includes the six remaining genera. The genus Sylvisorex appears to be polyphyletic, whereas species of the controversial genus Crocidura are monophyletic. The genus Suncus presumably originated in Africa. The monospecific genera Ruwenzorisorex and Scutisorex and the two representatives of Paracrocidura cluster with species of other genera. Grouping patterns of species from different continents suggest that there have been multiple exchanges between Africa and Eurasia. The time estimates of these exchanges, inferred from two independent fossil-based calibrations of a molecular clock, coincide with the time estimates for migration events in other mammalian taxa.
Keywords: African Research